1983
DOI: 10.1002/1097-0142(19831101)52:9<1760::aid-cncr2820520934>3.0.co;2-r
|View full text |Cite
|
Sign up to set email alerts
|

Cooperative groups and community hospitals. Measurement of impact in the community hospitals

Abstract: The Eastern Cooperative Oncology Group, composed of major cancer treatment centers, has an outreach program which involves community hospitals in ongoing cancer clinical trials. A prevalence survey was carried out in February 1981 among 104 community hospitals and 21 member institutions to determine the characteristics of patients being treated, their staffing, and reasons why patients were not on protocol studies. The survey sampled 25 (50) consecutive patients from community hospitals (member institutions). … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
21
0

Year Published

1983
1983
2016
2016

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 42 publications
(21 citation statements)
references
References 3 publications
0
21
0
Order By: Relevance
“…13 Together, these and earlier studies consistently show that once a patient has access to cancer care, the absence of an available clinical trial precludes participation for about half of all patients. 14,21,22 …”
Section: Understanding Barriers To Clinical Trial Participationmentioning
confidence: 99%
See 2 more Smart Citations
“…13 Together, these and earlier studies consistently show that once a patient has access to cancer care, the absence of an available clinical trial precludes participation for about half of all patients. 14,21,22 …”
Section: Understanding Barriers To Clinical Trial Participationmentioning
confidence: 99%
“…Studies have found that a common reason for patient ineligibility to available protocols is narrow eligibility criteria. 3,14,21,22,23,24 Trial eligibility attempt to satisfy two opposing criteria. On the one hand, eligibility must be sufficiently narrow to produce a treatment effect that is approximately consistent across the cohort.…”
Section: Understanding Barriers To Clinical Trial Participationmentioning
confidence: 99%
See 1 more Smart Citation
“…54 Although this may lead to the assumption that the treatment center has an influence on the treatment outcome, it has also been shown that within oncology trials, small community hospitals are able to generate treatment outcomes similar to the results obtained within large university hospitals. 53,[55][56][57][58] It is therefore more plausible that a difference in experience has influenced the relative favorable survival within specific hospitals, as it has been recognized that only a selection of hospitals participate in clinical trials. 1,59 Some older evidence exists on the capability of specialist centers to produce better treatment outcomes.…”
Section: Discussionmentioning
confidence: 99%
“…The referral base for this tertiary referral center comes from a five-state region of approximately 7 million persons. At this site, 17 Women eligible for this study were those diagnosed with breast cancer within the last 6 months and were selected from tumor registry data at each institution. Samples of trial-eligible and ineligible women from each site were identified.…”
Section: Subjectsmentioning
confidence: 99%